2015
DOI: 10.1002/2014jf003329
|View full text |Cite
|
Sign up to set email alerts
|

Recent glacier decline in the Kerguelen Islands (49°S, 69°E) derived from modeling, field observations, and satellite data

Abstract: Cap were compared to data from the early 1970s, providing a 40 year view of the differences in the spatial distribution of surface mass balance (SMB). To obtain additional regional data for the validation of our models, we analyzed MODIS images (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) to determine if our model was capable of reproducing variations in the transient snow line. The PDD model correctly simulated the variations in the snow line, the spatial variations in the SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 57 publications
4
49
0
Order By: Relevance
“…a −1 less negative glacier-wide mass balance between 2000 and 2009 (assuming extents and elevations from the year 2009). A threshold of 1 °C led to a better agreement with remotely sensed mass balance estimates (Table 1) and with ELA estimates from MODIS images56. Mass balance modeling with the regional circulation model MAR (Modèle Atmosphérique Régional)58 for 2011 also suggests that Tsnow/rain = 1.0 °C is suitable for the PDD at Kerguelen.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…a −1 less negative glacier-wide mass balance between 2000 and 2009 (assuming extents and elevations from the year 2009). A threshold of 1 °C led to a better agreement with remotely sensed mass balance estimates (Table 1) and with ELA estimates from MODIS images56. Mass balance modeling with the regional circulation model MAR (Modèle Atmosphérique Régional)58 for 2011 also suggests that Tsnow/rain = 1.0 °C is suitable for the PDD at Kerguelen.…”
Section: Methodsmentioning
confidence: 62%
“…As a consequence, they fail to reproduce the accelerating trend of glacier mass losses. An in depth analysis of precipitation events in models showed that (1) the distributions of precipitation intensity in the models differ significantly from observations, and, (2) even the MRI-ESM1 and MRI-CGCM3 models, which are considered the most comprehensive models in the Kerguelen region, do not reproduce the reduction in precipitation frequency and intensity observed in field data56. Finally, a distinct careful model selection was performed according to ref.…”
Section: Methodsmentioning
confidence: 99%
“…The focus is on the precipitation given its recent decline and major role in the glacier wastage reported at the Cook Ice Cap (Verfaillie et al 2015;Favier et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The Kerguelen Islands feature the Cook Ice Cap, a glacier located at a relatively low altitude and then directly influenced by changes in the oceanic and atmospheric circulations (Vallon 1987;Verfaillie et al 2015). Recently, Favier et al (2016) has shown that the glacier wastage in the Kerguelen Islands during the 2000s was among the most dramatic on Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Geological records of past alpine glacier variations may help close this data gap. Alpine glaciers, found on many Southern Ocean islands, are sensitive to ongoing climate change as demonstrated by their recent rapid retreat (Cook et al, 2005;Gordon et al, 2008;Glasser et al, 2011;Purdie et al, 2014;Verfaillie et al, 2015). This response is driven by changes in temperature and precipitation, which together determine surface mass balance and govern glacial erosion rates (Oerlemans, 2005;Herman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%